Discurso e força estética das notícias falsas: um estudo sobre a configuração do gênero fake news - Freire, Débora Fabianne da Silva (2019)
The making and spreading of false news are not new phenomena, but complex, strong, and adaptable to any society at any time. The production and dissemination of fake news continues, evolving and remaining, becoming a rhetorical device from which to derive from resilient effects in the real and virtual world. False news is inherent in multiple contexts involving sociability, gaining prominence in times of social instability, especially from the recent digital ambiences. Given the above, we sought, in this research, to identify a presence or not of false news of resources that put this verb-visual practice in the list of discursive genres. For this, we analyzed two situations that gained national visibility because they not only caused the impact of fake content produced and disseminated, but also the consequences generated from the repercussions recorded by the press and / or occurred in digital social networks: the Escola Base case, news false created and reflected in the traditional Brazilian press, especially in TVs and print newspapers, in the year 1994; and the ―gay kit‖ case, one of the most widely spread false news on social-digital networks, during an election campaign for Brazil's president in 2018. To check our hypothesis, compare them with classic authors, an example of Bakhtin, with his studies on dialogism and gender; in works that include or always current theme of false news; investigating changes in the forms of interaction, conversation and affect of the subjects; and in considering new and old forms of news production, circulation and manipulation. It concludes that false news is structured as a discursive genre, as it meets the precepts that configure a genre, in the Bakhtinian perspective. Thus, we detect that fake news has relatively stable aesthetic and discursive patterns; and acquired flexibilities, to achieve its discursive purposes and effects, from adaptations and changes that may arise in content, style and support, due to changes in communicative purposes, social context and integration of new technologies.